The Benefit of Creating a Culture of Student Leadership on School Aged Students - Frizzley, Selena M. (City University of Seattle (CityU), 2017)
This capstone paper will explore the different theories surrounding the development of leadership in students. Students will learn skills beginning from leadership vocabulary to living and practicing the leadership habits daily. Examining data from several schools that have successfully implemented leadership culture, I assess which models have had the best impact on student success. Drawing on the current research, I argue that the development and implementation of a leadership culture in grade school has a number of positive outcomes including attendance, increased results in literacy and numeracy achievement, behavioural improvements, future success in the workplace and for life. The capstone places particular interest in how leadership affects at risk populations such as First Nations, Metis and Inuit Learners and English Language Learners. Student leadership culture is an opportunity to give all students the chance to be leaders and develop lifelong leadership skills to benefit them throughout their lives.